Future of Education in the Era of Artificial Intelligence - Karki, Dipendra; Karki, Nirupan; Dahal, Rewan Kumar; Bhattarai, Ganesh (Journal of Interdisciplinary Studies, 2023)
The increasing use of Artificial Intelligence (AI) in the field of education has raised significant concerns regarding the potential displacement of educators by AI systems. The present study explores the diverse domain of artificiala intelligence’s influence on academia, examining its capacity to transform conventional educational frameworks. By conducting a methodical investigation using scholarly resources including IEEE Xplore, ACM Digital Library, ERIC, and Google Scholar, this study develops an extensive compilation of 135 publications that were published between January 2017 and June 2023. The results of the study demonstrate a dynamic environment in which artificial intelligence serves as both a stimulant and a challenge. The present analysis emphasizes the complex relationship between artificial intelligence (AI) and education, as evidenced by the theoretical underpinnings emphasized by Panaou et al. (2012), as well as the promise of AI advocated by Luckin et al. (2016). The research highlights the significance of adopting a well-rounded strategy, wherein artificial intelligence serves to enhance the responsibilities of educators rather than replace them.